2017
DOI: 10.1080/01480545.2017.1381109
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological effects of bisphenol A and nonylphenol on the freshwater cladoceransCeriodaphnia silvestrii and Daphnia similis

Abstract: Toxicities of bisphenol A (BPA) and nonylphenol (NP) to the neotropical freshwater cladocerans Ceriodaphnia silvestrii and Daphnia similis were studied under laboratory conditions. Acute exposures to BPA generated mean 48-h EC values of 14.44 (6.02-22.85) mg L for C. silvestrii and 12.05 (1.73-22.37) mg L for D. similis. When the organisms were exposed to acute doses of NP, mean 48-h EC values were 0.055 (0.047-0.064) mg L (C. silvestrii) and 0.133 (0.067-0.200) mg L (D. similis). Ceriodaphnia silvestrii was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
1
4
0
3
Order By: Relevance
“…In addition, the chronic tests performed with Ceriodaphnia dubia demonstrated high organism sensitivity to the analyzed compounds, since EDC samples before the Cl/UVC treatment led to 60% mortality on the third test day and 100% on the fourth day (data not shown). This is explained by E2, EE2, and BPA synergistic effects, since these compounds when analyzed separately in other studies display EC 50 values close to the EC 50 value applied in the present study [45][46][47]. For posttreatment samples (2 and 5 min), organism mortality reached 100% on the third test day, which may indicate the formation of toxic chlorine compounds during UV treatment [48,49].…”
Section: Estrogenic Activity Reductionsupporting
confidence: 83%
“…In addition, the chronic tests performed with Ceriodaphnia dubia demonstrated high organism sensitivity to the analyzed compounds, since EDC samples before the Cl/UVC treatment led to 60% mortality on the third test day and 100% on the fourth day (data not shown). This is explained by E2, EE2, and BPA synergistic effects, since these compounds when analyzed separately in other studies display EC 50 values close to the EC 50 value applied in the present study [45][46][47]. For posttreatment samples (2 and 5 min), organism mortality reached 100% on the third test day, which may indicate the formation of toxic chlorine compounds during UV treatment [48,49].…”
Section: Estrogenic Activity Reductionsupporting
confidence: 83%
“…Previous studies have shown a greater sensitivity of the tropical species C. silvestrii than some standard temperate test species, such as D. magna. For example, C. silvestrii was shown to be more sensitive than D. magna to the drugs acetaminophen, propranolol, and diclofenac (Oliveira et al 2018), to the organic compounds bisphenol and nonylphenol (Spadoto et al 2017), to the pesticides carbofuran and diuron (Mansano et al 2016), and the antimicrobials, florfenicol, and oxytetracycline (Freitas et al 2018). Unfortunately, there are no other toxicity data for zooplanktonic species or other tropical taxonomic groups exposed to fipronil and 2,4-D that also we could include in the SSD curves.…”
Section: Discussionmentioning
confidence: 99%
“…Hamlin và cộng sự (2015) cũng từng ghi nhận nước rỉ nhựa từ các túi nhựa PE có chứa NP và có thể làm suy giảm đến hơn 60% sức sống của loài cá Pseudochromis fridmani 15 . Tương tự, các phụ gia nhựa được sử dụng phổ biến như PTA và BPA cũng đã từng được ghi nhận có các tác động tiêu cực làm thay đổi kích thước cơ thể, suy giảm khả năng sinh sản, làm thay đổi hàm lượng lipid trong cơ thể và ức chế các hoạt động của các enzyme làm thay đổi các hoạt động sinh hóa của vi giáp xác D. magna, D. similis và Ceriodaphnia silvestrii 10,11,16,17 . Qua đó có thể thấy, sự hiện diện của nhựa trong môi trường, đặc biệt là môi trường nước có thể chứa đựng những rủi ro đối với hệ sinh thái thủy vực và sức khỏe cộng đồng.…”
unclassified